A variational approach to difference equations. Issue 12 (1st December 2016) - Heidarkhani, Shapour; Afrouzi, Ghasem A.; Caristi, Giuseppe; Henderson, Johnny; Moradi, Shahin
Abstract : In this paper, we are concerned with the existence of at least three distinct solutions for nonlinear difference equations with Dirichlet boundary conditions. The proof of the main result is based on variational methods. We also provide an example in order to illustrate the main results.